PEDAGOGICAL ASPECTS OF DEVELOPING INFORMATION COMPETENCE IN STUDENTS BASED ON AN INTEGRATIVE APPROACH - Ganiyeva O.S. (International Scientific and Current Research Conferences, 2023)
The article presents ideas about the pedagogical aspects of developing the information competence of future teachers. The basics of information competence in students, the information competence of students of pedagogic higher education institutions is aimed at professional development.